2007
DOI: 10.1176/ajp.2007.164.4.608
|View full text |Cite
|
Sign up to set email alerts
|

Neural Evidence for Enhanced Error Detection in Major Depressive Disorder

Abstract: These data implicate exaggerated early error-detection processes in the etiology and maintenance of major depressive disorder. Such processes may then recruit excessive neural and cognitive resources that manifest as symptoms of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(179 citation statements)
references
References 44 publications
20
151
4
Order By: Relevance
“…Reduced neural activation elicited by rewards in regions of the medial frontal cortex and striatum has been observed (Knutson et al, 2008;Kumar et al, 2008;Pizzagalli et al, 2009). Consistent with a negative bias, enhanced punishment or loss-related activity has also often been observed, particularly in studies employing event-related potentials (e.g., Chiu & Deldin, 2007;Holmes & Pizzagalli, 2008), but equally so has been attenuated loss-related activity (Steele et al, 2007).…”
Section: Methods Subjectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Reduced neural activation elicited by rewards in regions of the medial frontal cortex and striatum has been observed (Knutson et al, 2008;Kumar et al, 2008;Pizzagalli et al, 2009). Consistent with a negative bias, enhanced punishment or loss-related activity has also often been observed, particularly in studies employing event-related potentials (e.g., Chiu & Deldin, 2007;Holmes & Pizzagalli, 2008), but equally so has been attenuated loss-related activity (Steele et al, 2007).…”
Section: Methods Subjectsmentioning
confidence: 93%
“…A variety of effects have been observed with different paradigms, which were briefly discussed in the introduction. Typically, the paradigms that are employed follow a straightforward Pavlovian format in which a stimulus precedes a rewarding outcome (e.g., Kumar et al, 2008) or are analyzed with a direct focus on important parameters, such as selection, anticipation, and outcome (e.g., Chiu & Deldin, 2007;Knutson et al, 2008;Smoski et al, 2009). Collectively, these findings have so far resisted a straightforward unifying account and are generally not discussed in terms of regret or counterfactual cognition.…”
Section: Decision Makingmentioning
confidence: 99%
“…36,37 This reduced conflict monitoring and potentiated error processing in individuals with MDD have been associated with dorsal ACC hypoactivation and rostral ACC hyperactivation, respectively. 20,36,38,39 Accordingly, these findings point to regionspecific hypo-and hyperactivation within frontocingulate pathways in people with depression and are consistent with literature emphasizing functional differentiation between different ACC subdivisions.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains unclear whether this dorsal activation is either decreased or increased during cognitive control operations engaged during the processing of emotional stimuli in currently or remitted depressed patients (Joormann & Gotlib, 2008). While some studies reported hyperactivity in these dorsal regions in depressed patients during cognitive control operations (Chiu & Deldin, 2007;Harvey et al, 2005;Holmes & Pizzagalli, 2008a;Luu, Flaisch, & Tucker, 2000;Liotti, Woldorff, Perez, & Mayberg, 2000), other studies found depressionrelated hypoactivity in these same areas, including the DLPFC and the dACC (Holmes & Pizzagalli, 2008b;Vanderhasselt & De Raedt, 2009). This discrepancy might stem from the fact that these studies focussed on different aspects of cognitive control, including proactive and reactive mechanisms (Braver, Gray, & Burgess, 2007).…”
Section: Introductionmentioning
confidence: 98%